Prevalence and Covariates of Undiagnosed Hypertension in the Adult Population of Puducherry, South India - Bharati, DR; Nandi, P; Yamuna, TV; Lokeshmaran, A; Agarwal, L; Singh, JB; Basu, M; Das, P; Pal, R (Nepal Journal of Epidemiology, 2012)
Background Globally the prevalence of both hypertension and pre-hypertension are increasing and pre-hypertension has been associated with higher cardiovascular risk. The objective of this study was to find out the prevalence of undiagnosed hypertension and pre-hypertension and associated covariates among adults of rural and urban area of Puducherry. Material and Methods A population based cross-sectional study was carried out in the field practices area of Department of Community Medicine, Mahatma Gandhi Medical College and Research Institute without intervention. Results Among 856 participants, 27.6 percent were hypertensive and 57 percent pre-hypertensive; the magnitude of both stage 1 and stage 2 hypertension increased with the age. Of the hypertensives, 26.3 and 28.7 percent were from rural and urban area respectively, whereas in pre-hypertension the corresponding figures were 61 and 53.4 percent. Significantly increased risk of hypertension was noted among adults with increasing age, having less than six members in the family, suffering from obesity (general and abdominal obesity) and living sedentary life. On the other hand, the probability of having increased risk of pre-hypertension was significantly higher among adults living in the rural areas, having non-vegetarian dietary habit, suffering from obesity (general and abdominal obesity), living sedentary life and having family history of hypertension. Multivariate logistic regression however showed significant correlation of hypertension with increasing age, sedentary lifestyle, tobacco addiction and obesity (general and central). Significant correlates of pre-hypertensive were rural residence, sedentary living habits, family history of hypertension, tobacco addiction and obesity (general and central). Conclusion The present findings show high prevalence of hypertension and pre-hypertension among population of Puducherry in South India. DOI: http://dx.doi.org/10.3126/nje.v2i2.6576 Nepal Journal of Epidemiology 2012;2(2):191-199